Neutralizing antibodies against poliovirus serotypes among children in southwest Nigeria (2005)
In May 1988, the World Health Assembly resolved to eradicate poliomyelitis globally by the year 2000. Despite the reported success in national immunization days, acute flaccid paralysis surveillance and accelerated efforts to meet the deadline including ‘mopping-up’ were executed in 1999 and subsequent years. Nigeria remains one of the major reservoirs for wild poliovirus transmission. Neutralizing antibody titre to the three poliovirus serotypes was determined among children from different communities in southwest of Nigeria, and analysed by age, gender and location. About 0.5–2 ml of blood sample was collected by venepuncture from each child. Aliquot of serum from each blood sample was inactivated prior to neutralization test by the beta method for poliovirus antibodies. A total of 347 (59.6 per cent) out of 500 and 82 children enrolled for the study had at least antibody titre of 1:8 against each of the three poliovirus serotypes. Immunity level to the three poliovirus serotypes increased with age and peaked in children aged 4–6 years. Seven (53.8 per cent) out of 13 unvaccinated children tested in the study had detectable neutralizing antibody to the three serotypes. Immunity pattern of P2 > P1 and P3 was observed but no correlation between gender and antibody to the poliovirus serotypes. The populations had 59.6 per cent herd immunity for the three poliovirus serotypes. In a country with high incidence of poliomyelitis this situation leaves a high number of non-immunized children at the risk of infection with one or more poliovirus serotypes.